(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
The aim of present research was to study the genetic diversity among Asparagus species and its cultivars using morphological characteristics and RAPD markers. In-vitro and field experiments of 14 germplasm sources of Asparagus species and its cultivars were conducted at the Kohat University of Science and Technology to estimate the comparative performance. Highest genotypic variance, phenotypic variance, genotypic and phenotypic coefficient of variance were observed in shoot height in shoot related traits were 318.40, 320.30, 939.34 and 944.96, respectively, whereas highest values for root related traits were observed in root length that were 21.84, 22.35, 141.60 and 144.91 respectively. Among the shoot related traits maximum heritability, genetic advance and genetic gain were calculated for shoot length, while in root related traits these characters were highest for root dry weight. RAPD markers were used to evaluate genetic diversity analysis of 14 germplasm sources of Asparagus species and its cultivars. RAPD markers generated a total of 247 bands, of these 239 bands were polymorphic with average of 34.1 bands per primer. Cluster analysis based on Neighbor Joining methods showed that wild species (A. adsendens, A. densiflorus, A. capitatus, A. gracelus, A. plumosus, A. racemosus and A. setaceus) were genetically distant from A. officinalis and its cultivars (Abril, Apollo, Gersengum, Huchel, Para seletion and Taranga). The results of the present investigations could be particularly used for authentic identification and would be useful for evaluation of genetic improvement of Asparagus species and its cultivars. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 13-24